Imidacloprid Impairs Glutamatergic Synaptic Plasticity and Desensitizes Mechanosensitive, Nociceptive, and Photogenic Response of Drosophila melanogaster by Mediating Oxidative Stress, Which Could Be Rescued by Osthole. - Liu, C.H.; Chen, M.Y.; Cheng, J.; Chuang, T.N.; Liu, H.P.; Lin, W.Y. (International journal of molecular sciences, 2022)
Imidacloprid (IMD) is a widely used neonicotinoid-targeting insect nicotine acetylcholine receptors (nAChRs). However, off-target effects raise environmental concerns, including the IMD's impairment of the memory of honeybees and rodents. Although the down-regulation of inotropic glutamate receptor (iGluR) was proposed as the cause, whether IMD directly manipulates the activation or inhibition of iGluR is unknown. Using electrophysiological recording on fruit fly neuromuscular junction (NMJ), we found that IMD of 0.125 and 12.5 mg/L did not activate glutamate receptors nor inhibit the glutamate-triggered depolarization of the glutamatergic synapse. However, chronic IMD treatment attenuated short-term facilitation (STF) of NMJ by more than 20%. Moreover, by behavioral assays, we found that IMD desensitized the fruit flies' response to mechanosensitive, nociceptive, and photogenic stimuli. Finally, the treatment of the antioxidant osthole rescued the chronic IMD-induced phenotypes. We clarified that IMD is neither agonist nor antagonist of glutamate receptors, but chronic treatment with environmental-relevant concentrations impairs glutamatergic plasticity of the NMJ of fruit flies and interferes with the sensory response by mediating oxidative stress.